(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Based on Base Transceiver Station (BTS) and Mobile Station (MS) radiation, the residence of Kushtia district in Bangladesh is usually concerned with the potential health effects. Inhabitants, living in this part of Bangladesh are using communication, internet browsing, and other related uses with the help of mobile cellular communication system. The subscriber needed improving radio coverage, excellent communication networks, and quicker speed for internet browsing with the recent developments in mobile cellular communication technologies. To meet this demand, service providers of mobile cellular companies set up several BTS, which emit harmful radiation that has extremely detrimental impact on the human body. Through this paper, the effects of electromagnetic radiation of MS as well as BTS on the human body have been analyzed and Electromagnetic Field (EMF) radiation levels of MSs along with BTSs located in this region have been measured. These measurements have been compared with the measured value provided by the World Health Organization (WHO) and International Commission of Non-Ionizing Radiation Protection (ICNIRP). Finally, a cross-sectional analysis was carried out to evaluate the understanding and self-reported health risks of Electromagnetic waves (EMW) radiation emittedfrom the MS as well as BTS among the inhabitants of this region who are living near and a little away from BTS.